Reducing Treatment Burden for Age-Related Macular Degeneration Patients: A Systematic Review of Ranibizumab Port Delivery System: Oral Presentation - Observational Study - General practitioner - Paramitha, Dewa Ayu Anggi; Putri, Ajeng Kartika Ayu; Ardhia, Seruni Hanna; Jutamulia, Jovita (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Ranibizumab port delivery system (PDS) is a newly developed method that provides a continuous, long-term supply of ranibizumab into the vitreous, reducing the burden of monthly intravitreal injection visits for neovascular age-related macular degeneration (nAMD) patients. This review aims to evaluate the efficacy and safety of ranibizumab PDS in nAMD. Methods An extensive literature search was performed on 4 online databases: PubMed, Cochrane, ProQuest, and ScienceDirect. The inclusion criteria are human studies comparing ranibizumab port delivery system and intravitreal ranibizumab, English language, with full-text journal available. The main outcome measurements are best-corrected visual acuity (BCVA) in Early Treatment Diabetic Retinopathy Study (ETDRS) letters, central foveal thickness (CFT), and adverse events. Results Two randomized controlled trials (RCTs) with a total of 638 adults were evaluated. At week 96, ranibizumab PDS reported observed mean BCVA changes from baseline (-1.0; +4.2; ETDRS letters) compared to monthly intravitreal ranibizumab (-1.1; +6.1; ETDRS letters). However, there was an increase in mean CFT changes from baseline (+9.9; +22.3 vs ?1.3; ?35.8, ?m) and severe adverse events frequency (22; 4 vs 4; 0) with ranibizumab PDS versus monthly intravitreal ranibizumab, respectively. Conclusion Ranibizumab PDS showed comparable visual outcomes to intravitreal ranibizumab while demonstrating inferior anatomical outcomes and higher incidence of severe adverse effects. Despite this, with fewer treatment visits required for up to 24 weeks, ranibizumab PDS can potentially reduce the treatment burden in nAMD patients with poor compliance. Further studies are needed to provide better patient eligibility guidelines and recommendations for adverse event management of ranibizumab PDS.